Motivational differences in athletes trained by coaches of different motivational and leadership profiles - Baric, R.; Bucik, V. (Kinesiology, 2009)
Coaches of different profiles influence athletes` sports motivation differently. The aim of this paper was to investigate the coaches` contribution to the motivational structure of athletes from team sports. Using the coaches` self-evaluations of goal orientation and intrinsic motivation and the athletes` evaluations of their coaches` leadership styles, the two types of coaches were identified. Discriminant analysis showed the differences in motivational structure between athletes trained by the coaches from either one or the other group. The athletes who were trained by the more athlete-directed, low ego-oriented coaches showed a preferable motivational pattern; they perceived the mastery motivational climate in their teams, were higher on intrinsic motivation, their task goal orientation was high and ego goal orientation was elevated. The athletes trained by the less athlete-directed and high ego-oriented coaches perceived fewer signs of the mastery motivational climate in their teams, were less intrinsically motivated, and their task orientation and ego goal orientation were lower. The motivational structure profiles of the athletes from the second group and their coaches seem incongruent and this incompatibility might induce athletes` lower motivation.